Abdominal normothermic regional perfusion in controlled donation after circulatory determination of death liver transplantation: Outcomes and risk factors for graft loss. Issue 4 (21st December 2021) - Hessheimer, Amelia J.; de la Rosa, Gloria; Gastaca, Mikel; Ruíz, Patricia; Otero, Alejandra; Gómez, Manuel; Alconchel, Felipe; Ramírez, Pablo; Bosca, Andrea; López‐Andújar, Rafael; Atutxa, Lánder; Royo‐Villanova, Mario; et al.
Abstract : Postmortem normothermic regional perfusion (NRP) is a rising preservation strategy in controlled donation after circulatory determination of death (cDCD). Herein, we present results for cDCD liver transplants performed in Spain 2012–2019, with outcomes evaluated through December 31, 2020. Results were analyzed retrospectively and according to recovery technique (abdominal NRP [A‐NRP] or standard rapid recovery [SRR]). During the study period, 545 cDCD liver transplants were performed with A‐NRP and 258 with SRR. Median donor age was 59 years (interquartile range 49–67 years). Adjusted risk estimates were improved with A‐NRP for overall biliary complications (OR 0.300, 95% CI 0.197–0.459, p < .001), ischemic type biliary lesions (OR 0.112, 95% CI 0.042–0.299, p < .001), graft loss (HR 0.371, 95% CI 0.267–0.516, p < .001), and patient death (HR 0.540, 95% CI 0.373–0.781, p = .001). Cold ischemia time (HR 1.004, 95% CI 1.001–1.007, p = .021) and re‐transplantation indication (HR 9.552, 95% CI 3.519–25.930, p < .001) were significant independent predictors for graft loss among cDCD livers with A‐NRP. While use of A‐NRP helps overcome traditional limitations in cDCD liver transplantation, opportunity for improvement remains for cases with prolonged cold ischemia and/or technically complex recipients, indicating a potential role for complimentary ex situ perfusion preservation techniques. Abstract : Results of more than 500 liver transplants performed after controlled donation after circulatory determination of death followed by postmortem normothermic regional perfusion are reported and analyzed to identify independent risk factors for graft loss.